1976
DOI: 10.1037/0033-295x.83.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and linguistic processes in speech perception: Inferences from six fusions in dichotic listening.

Abstract: A number of phenomena in speech perception have been called fusion, but little effort has been made to compare these phenomena in a systematic fashion. The present paper examines six of them. All can be exemplified using the syllable /da/ as in dot, and all occur during dichotic listening. In each type of fusion, the robustness of the fused percept is observed against variation in three parameters: the relative onset time of the two opposite-ear stimuli, their relative intensity, and their relative fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
155
5
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(173 citation statements)
references
References 86 publications
11
155
5
2
Order By: Relevance
“…The paradigm has been transposed to the study of written language perception since the work by Prinzmetal (1981) and more recently with the study of letter migrations (Kolinsky, 1992;Mozer, 1983;McClelland & Mozer, 1986). Antecedents of the paradigm in the domain of spoken language processing include the study of fusions by Cutting (1976). Along these lines it was observed that dichotic presentation of a pair of spoken words may lead to the mistaken perception of a target (Kolinsky, Morais, & Cluytens, 1995).…”
Section: A Speech-processing Deficit: Which Focus On Processing and Wmentioning
confidence: 99%
“…The paradigm has been transposed to the study of written language perception since the work by Prinzmetal (1981) and more recently with the study of letter migrations (Kolinsky, 1992;Mozer, 1983;McClelland & Mozer, 1986). Antecedents of the paradigm in the domain of spoken language processing include the study of fusions by Cutting (1976). Along these lines it was observed that dichotic presentation of a pair of spoken words may lead to the mistaken perception of a target (Kolinsky, Morais, & Cluytens, 1995).…”
Section: A Speech-processing Deficit: Which Focus On Processing and Wmentioning
confidence: 99%
“…One of the tasks could in principle provide evidence for:a stage of phonetic feature extraction. It has been shown that, when syllables beginning with a plosive are presented dichotically, most of the recognition errors consist apparently in blending one feature of one stimulus with another feature of the other stimulus, as in , Studdert-Kennedy & Shankweiler, 1970;Cutting, 1976). We inspected whether Portuguese illiterates and literates make feature blendings significantly above chance and in the same proportion or not, in a similar Situation (Morais, Castro, Scliar-Cabral, Kolinsky, & Content, in press).…”
Section: Phonetic Awareness and Speech Processingmentioning
confidence: 99%
“…Separation in space has also resulted in less integration in several studies employing speech (Cherry & Taylor, 1954;Huggins, 1964;Schubert & Schultz, 1962). However, integration of lateralized speech components, which are presumably perceived as arriving from separate spatial locations, has been demonstrated (Broadbent, 1955;Broadbent & Ladefoged, 1957;Cutting, 1976;Rand, 1974).…”
mentioning
confidence: 99%
“…Many ofthe same attributes that have been demonstrated to be important for segregation of simple sounds also appear to playa role in segregation and grouping of speech sounds and are of especial utility in segregating the speech ofcontemporaneous speakers. Again, asynchrony ofonsets and inharmonicity have been found to promote segregation of the components (Cutting, 1976;Darwin, 1981;Darwin & Gardner, 1986;Scheffers, 1983). Spectral distance and trajectories of spectral change greatly influence speech source integration and segregation (Dorman, Cutting, & Raphael, 1975).…”
mentioning
confidence: 99%
See 1 more Smart Citation